Correlation between morphology and performance of cellulose nanofibril-based films - Liqing Wei; Huiyang Bian; Umesh P. Agarwal; Ronald C. Sabo; Laurent M. Matuana; Nicole M. Stark (Current Research in Green and Sustainable Chemistry, 2023)
Cellulose nanofibrils (CNFs) were produced from bleached eucalyptus kraft pulp using microfluidization varying the number of passes through the microfluidizer. CNFs were processed into dry films to elucidate the effect of CNFs morphology on the physical, optical and barrier properties of the films. As the number of passes through the microfluidizer increased, the fibril diameter and degree of polymerization decreased. A higher number of passes produced CNFs with smaller diameter resulting in CNF films with smaller root mean surface (RMS) roughness, higher tensile strength and Young's modulus, and higher transparency. CNF films with lower porosity had lower water vapor permeability (WVP) at 50% RH (better barrier properties), but the number of passes did not significantly affect water vapor permeability at 90% RH or oxygen permeability at 50% RH or 90% RH. Increasing the number of microfluidization passes resulted in CNF films with higher density, lower crystallinity, and higher water accessibility. The results suggest that the physical properties, such as density, of the film were more dominant for the mechanism of WVP compared with crystallinity and water accessibility. A model of water vapor transmission through the CNF film was proposed. By establishing a relationship between CNFs morphology and performance characteristics of corresponding films, especially for barrier properties, insights were obtained that would be beneficial for food packaging applications.